PENDUGAAN PARAMETER GENETIK HASIL DAN KOMPONEN HASIL GALUR - GALUR PADI LOKAL ASAL BANTEN - Sahiral Yakub; Kartina A.M. Kartina; Sulastri Isminingsih; M. L. Suroso (JURNAL AGROTROPIKA, 2012)
The experiment was conducted to examine genetic parameter of yield and yield components of local rice lines. The experiment was conducted at field research Singamerta BPTP Banten from July up to January 2009.The treatment was arranged in randomized complete block design with three replications and 24 local rice lines with 3 check varieties (Hawara, Sarinah, and Ciherang). The result showed that observed characters had high and moderate heritabilities and highly expected selection advanced at 10% (1.76) selection intensi-ties. The selection would be applied in early generation, respectively.  Key words: genetic parameters, local rice lines, Banten